Rye bread intake improves oxidation resistance of LDL in healthy humans - Söderholm, P.P.; Alfthan, G.; Tikkanen, M.J.; Adlercreutz, H. (Atherosclerosis, 2012)
► Rye bread intake increased oxidation resistance of LDL. ► Alkylresorcinol concentration in LDL increased significantly following rye bread intake. ► The increased alkylresorcinol concentration did not correlate with oxidation resistance of LDL. Oxidatively modified LDL particles contribute to atherogenic development and therefore dietary interventions for promoting oxidation resistance of LDL are of interest. The capacity of LDL to resist oxidation can be determined ex vivo by exposing isolated LDL particles to copper ions and measuring the formation of conjugated dienes by spectrophotometry. The aim of this trial was to determine the effect of none versus high intake of rye bread on the oxidation resistance of LDL in healthy humans while otherwise on habitual diet. Sixty-three healthy subjects excluded rye products for one week (baseline), followed by a stepwise addition of rye bread from 99g/d during the first two weeks to 198g/d during the following two weeks. Additionally plant sterols were incorporated into the rye bread for half of the subjects to study cholesterol-lowering. The resistance of LDL against copper-induced oxidation was determined at baseline and at the end of the rye-period by monitoring formation of conjugated dienes. We observed a significant increase in the oxidation resistance of LDL, determined as a prolongation of the lag time (P<0.001) and decrease in the slope of the propagation phase (P=0.048) from baseline to the end of the rye-period without changes in vitamin E concentration. We observed no significant differences in the oxidation resistance of LDL between subjects who did or did not receive plant sterols. Rye bread intake improved significantly the oxidation resistance of LDL. Further studies are needed to clarify the protective mechanism(s).